Retrospective on: Constraint-Based Automatic Test Data Generation - Offutt, Jeff; DeMillo, Richard (IEEE transactions on software engineering, 2025)
This article is a retrospective reflection on our paper Constraint-Based Automatic Test Data Generation (DeMillo and Offutt, 1991), which was selected by the editorial board of the IEEE Transactions on Software Engineering as one of the most influential papers of the second decade of the journal. Published in 1991, this paper introduced a novel approach to automated test case generation using symbolic execution and constraint-solving techniques, a fundamental shift in how to approach software testing. The retrospective explores the impact of the paper on the development of mutation testing, the creation of the Mothra toolset, the evolution of test automation practices, and the technical innovations that made the paper a cornerstone of modern testing research. Beyond its technical contributions, the article has become known for its role in fostering a culture of rigorous systems-oriented research that continues to influence both academia and industry. This reflection highlights the enduring relevance of Constraint-Based Test Case Generation and its role as a foundational work in the field of software engineering.